A contingent value? The changing role of autonomy in law and policy on AIDS - John A. Harrington (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
This essay examines the changing role of the ethical value of autonomy in law and policy relating to AIDS in a number of European jurisdictions. In the early years of the epidemic the autonomy of infected and at-risk persons, and of social groups was promoted as a means of reducing the spread of HIV in the general population. Accordingly autonomy was deemed worthy of respect for instrumental reasons. This means-end calculation was premised on the lack of medical therapies, as well as the need to avoid discrimination in order to prevent at-risk persons from going underground as far as health care systems were concerned. In law this instrumentalisation of autonomy was reflected in a specific application of the proportionality test, i.e. to impose coercive or discriminatory measures would be disproportionate, or even inimical, to the end of reducing the spread of HIV. This was a contingent analysis, strongly informed by the state of medical knowledge at the time, as well as by the relative power of professionals, health bureaucrats and lay activists. With the introduction of effective therapies such as Highly Active Retroviral Therapy (HAART) and Zidovudine (AZT) the terms of the proportionality analysis have changed decisively. As a result, it is now more likely than before that coercive measures will be implemented.
Keywords: 300